Resection of an Optic Canal Meningioma through a Contralateral Subfrontal Approach with Endoscopic Assistance: A 2D Operative Video - Labidi, Moujahed; Watanabe, Kentaro; Bernat, Anne-Laure; Hanakita, Shunya; Froelich, Sébastien (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective To review the use of the contralateral subfrontal approach for the resection of an optic canal meningioma.Design Operative video.Results A meningioma, located in the inferomedial side of the optic canal (Fig. 1), was found to cause significant visual deterioration. The subfrontal route was preferred to expose the tumor without mobilization of the optic nerve. Drilling of the anterior limb of the chiasmatic sulcus (limbus sphenoidale) provided adequate exposure of the medial aspect of the optic canal. Gross total resection (Simpson II) of the tumor was accomplished, and endoscopic assistance allowed identification and coagulation of an infiltrated dura mater in the chiasmatic sulcus and tuberculum sellae.Conclusion The subfrontal approach grants an optimal surgical trajectory to the contralateral chiasmatic sulcus and optic nerve. When the medial side of the optic canal is drilled, tumors extending into the optic canal can be safely resected, under direct visualization of the inferomedial side of the optic nerve. Breach into the sphenoid sinus can occur during drilling of the anterior limb of the chiasmatic sulcus. Endoscopic assistance can provide a better view on blind areas of the surgical field, including the depth of the optic canal (Fig. 2).The link to the video can be found at: https://youtu.be/fS2udUCPH1g.
Keywords: optic canal; meningioma; endoscopic assistance; skull base